RELASI GENDER PADA MASYARAKAT ADAT LAMPUNG PAGAR DEWA - Asyrofi, Imam; Githo, Githo; Iswanto, Iswanto; azhar, immawan (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The indigenous people of Lampung Pagar Dewa Tulang Bawang Barat distinguish between men and women, men in the public domain, and women in the domestic sphere. The gender distinction in the